Purification, characterization, crystal structure and NO production inhibitory activity of three new sesquiterpenoids from homalomena occulta. Issue 11 (24th October 2018) - Zhang, Qi; Ma, Li; Qu, Zhaoxia; Hou, Guige; Wang, Yanan; Wang, Chunhua; Zhao, Feng
Abstract : Three new sesquiterpenoids were isolated from homalomena occulta, and their structures were confirmed based on extensive spectroscopic analyses and single‐crystal X‐ray diffraction. The three compounds were evaluated for their activity against the LPS‐induced production of nitrogen oxide (NO) in RAW 264.7 cells. Abstract : Two new isodaucane‐type sesquiterpenoids, namely (1 R, 4 S, 5 S, 6 R, 7 S, 10 R )‐isodauc‐6, 7, 10‐triol, C15 H28 O3, (1 ), and (1 R, 4 S, 5 S, 6 S, 7 S, 10 R )‐isodauc‐6, 7, 10‐triol, (2 ), and a new eudesmane‐type sesquiterpenoid, 1β, 4β, 5α‐trihydroxyeudesmane, (3 ), were obtained from the rhizomes of homalomena occulta with the aid of column chromatography. Their structures were elucidated based on extensive spectroscopic analyses, including 1D NMR, 2D NMR and HRESIMS. The structure of (1 ) was confirmed by single‐crystal X‐ray diffraction and the absolute configuration was assigned with respect to that of the precursor. The single‐crystal structure reveals that adjacent molecules of (1 ) embrace through two groups of intermolecular O—H…O hydrogen bonds to generate a two‐dimensional sheet with a 6 3 ‐net topology. The three compounds were evaluated for their activity against lipopolysaccharide‐induced production of nitrogen oxide (NO) in RAW 264.7 cells, and (1 ) showed an inhibitory effect on NO production, with IC50 values of 5.7±0.22 µ M .